Meningkatkan Pemahaman Bangun Datar Siswa Kelas II SD Melalui Evaluasi Kognitif dan Psikomotorik - Muhammad Fathur Ardana; Chandra Chandra; Salmaini Safitri Syam (Lembag, 2025)
This study aims to improve the understanding of the concept of plane figures in grade 2 elementary school students through a cognitive and psychomotor evaluation approach. The problem faced is the low understanding of students towards the characteristics and forms of plane figures, which has an impact on mathematics learning outcomes. The method used in this study is classroom action research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection. Cognitive evaluation is carried out through a written test that measures students' conceptual understanding, while psychomotor evaluation involves practical activities such as drawing and forming plane figures using simple tools. The results of the study showed a significant increase in students' understanding after intervention through both types of evaluation. Students became more active, enthusiastic, and able to connect abstract concepts with concrete activities. Thus, cognitive and psychomotor evaluations have proven effective in improving the understanding of plane figures in grade 2 elementary school students.